PulseNet: The Molecular Subtyping Network for Foodborne Bacterial Disease Surveillance, United States - Bala Swaminathan; Timothy J. Barrett; Susan B. Hunter; Robert V. Tauxe (Emerging Infectious Diseases, 2001)
PulseNet, the national molecular subtyping network for foodborne disease surveillance, was established by the Centers for Disease Control and Prevention and several state health department laboratories to facilitate subtyping bacterial foodborne pathogens for epidemiologic purposes. PulseNet, which began in 1996 with 10 laboratories typing a single pathogen (Escherichia coli O157:H7), now includes 46 state and 2 local public health laboratories and the food safety laboratories of the U.S. Food and Drug Administration and the U.S. Department of Agriculture. Four foodborne pathogens (E. coli O157:H7; nontyphoidal Salmonella serotypes, Listeria monocytogenes and Shigella) are being subtyped, and other